Effect of soil matric potential on carrot production throughout the active root development period - Silva, Washington Luiz de Carvalho; Vieira, Jairo Vidal; Carrijo, Osmar Alves (Pesquisa Agropecuaria Brasileira, 2014)
An irrigation experiment was carried out in Brasilia, DF, to determine the optimum soil moisture level to produce carrots (Daucus carota L.). The crop was submitted to minimum water potentials in the soil of -0,19. -0,24, -0,29 and -0,33 bar. Treatments started 40 days after sowing and the roots were harvested 110 days later. Harvested roots were classified into total and commercial production. Both data differed only for treatments with -0,33 bar. It was concluded that good carrot yields can be obtained by irrigating only after the available soil water is reduced to 60% or when the soil water matric potential reaches -0,29 bar.